Bentuk Tindak Tutur Ekspresif dalam Tayangan Mata Najwa Serial “Gaduh Tiga Periode”. - Laili Etika Rahmawati; Zulfa Destia Isnaini; Zahy Riswahyudha Ariyanto (Badan Pengembangan dan Pembinaan Bahasa, 2023)
Najwa's eyes are often the basis for people's opinions and feelings being expressed. The expressive speech acts in Mata Najwa's talk show entitled